A family study of spontaneous sister chromatid exchange frequency. - Cohen, M M (1982)
The frequency of spontaneous sister chromatid exchanges (SCEs) was determined in PHA-stimulated peripheral lymphocytes of 52 individuals, comprising 12 complete 2-generation pedigrees. Neither intraindividual variation between replicate cultures established from the same blood sample nor variation among samples from the same individual initiated at different times was significant. However, familial factors affecting mean SCE frequencies were indicated by detection of significant differences among, but not within, families. Although sample sizes were small, a genetic contribution to the SCE frequency was suggested by the observed pattern of familial correlations.